Crony Capitalism in Ukraine : Relationship between Political Connectedness and Firms' Performance - Balabushko, Oleksii (World Bank, Washington, DC, 2018)
This study combines firm-level data and data on politically exposed people to explore correlation between firms' political connectedness and their economic performance in Ukraine. First, it estimates the share of politically connected firms in Ukraine's economy. Second, the study looks at how different the performance of politically connected firms is from that of their nonconnected peers. The analysis finds that 2 percent of firms are politically connected, but they control over 20 percent of the total turnover and over 25 percent of the assets of all Ukrainian companies. Over the past two decades, politically connected firms used various channels to access economic rents: public procurement, subsidized loans, transfers from the budget, trade regulations that restrict imports, privileged access to state assets through privatizations, and beneficial tax regimes. There is a strong negative correlation between political connection and productivity. Politically connected firms are larger and employ more people, but they are less productive and grow slower in turnover and job creation. This may likely account for lower economic growth and less competitive economy.